The role of identity in a multilevel interdependence in international relations: exploring popular understandings of international politics - Alrasheed, Rashed Ahmed; Al-Shamli, Khalid Amur Salim; Benabdallah, Aicha Kada; Abed Al-Ameri, Ibtisam Mohammed; Elshorbagy, Nahla (Frontiers in Political Science, 2025)
This study investigates the role of identity as a critical factor in mediating the relationship between local and regional politics within the broader context of international relations (IR). While identity is frequently acknowledged as a catalyst for political instability and conflict, its function in fostering interdependence across political levels remains underexplored, particularly through empirical research. To address this gap, the study adopts a quantitative methodology, drawing on theories of identity politics and interdependence. A structured survey was administered to assess public perceptions of identity's influence on international engagement and its bridging role between domestic and regional political dynamics. The findings indicate that respondents identify several key mechanisms through which identity fosters interconnection: cross-border solidarity, state-building processes, political legitimacy and survival, identity discourse in foreign policy, and the influence of non-state actors. Notably, participants expressed concern that instrumentalizing identity in state-building poses security threats at various levels—local (37.2%), national (18.2%), international (11.7%), and regional (9%). The data also reveal that ideological divides between social movements and state authorities, as well as transnational alliances between non-state actors and foreign powers, undermine state legitimacy and stability. The study contributes to theoretical and empirical debates in IR by demonstrating how identity shapes political interactions across multiple governance levels. It emphasizes the importance of public perceptions in legitimizing political engagement and reveals how identity can simultaneously serve as a unifying and destabilizing force in regional and international contexts.